A Principled Approach to the Construction of Risk Assessment Categories: The Council of State Governments Justice Center Five-Level System - Kroner, Daryl G. (International journal of offender therapy and comparative criminology, 2020)
Consistent risk category placement of criminal justice clients across instruments will improve the communication of risk. Efforts coordinated by the Council of State Governments (CSG) Justice Center led to the development of a principled (i.e., a system based on a given set of procedures) method of developing risk assessment levels. An established risk assessment instrument (Level of Service Inventory-Revised [LSI-R]) was used to assess the risk-level concordance of the CSG Justice Center Five-Level system. Specifically, concordance was assessed by matching the defining characteristics of the data set with its distribution qualities and by the level/category similarity between the observed reoffending base rate and the statistical probability of reoffending. Support for the CSG Justice Center Five-Level system was found through a probation data set (N = 24,936) having a greater proportion of offenders in the lower risk levels than a parole/community data set (N = 36,303). The statistical probabilities of reoffending in each CSG Justice Center system risk level had greater concordance to the observed Five-Level base rates than the base rates from the LSI-R original categories. The concordance evidence for the CSG Justice Center Five-Level system demonstrates the ability of this system to place clients in appropriate risk levels.